(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
This study examines the sales tax audit mechanism and its impact on financial sustainability in Iraq (the case of telecommunications companies) and investigates the main problems in the tax audit process with regard to the appropriateness of the type of audit used, the appropriateness of methods for selecting the audit case, and audit examination techniques used. Mixed in order to achieve research objectives and answer research questions. Specifically, the methods used in the study include submitting questions to auditors and tax investigators, and documentary and literary analysis. Using these research methods, the results of the study reveal that the sales tax audit mechanism is still undeveloped and uses a minimal set of tax audit activities that are conducted in order to address specific risks, in contrast to the concept of the sales tax audit mechanism which is a tool that improves voluntary compliance and increases performance future revenue and thus achieving financial sustainability by educating and helping taxpayers understand their tax obligations. Good interaction between tax auditors and taxpayers, in the end, the study presents the measures that can be taken by the public tax authority to alleviate the problems in the tax audit process.